Response of growth, yield and berry composition to basal leaf removal in Jaen grapevine - Andrade, I. (2005)
Results from a leaf removal experiment located at Dão Winegrowing region of Portugal are presented. Three intensity levels of defoliation (control non-defoliated, leaves removed up to the third basal node and up to the sixth basal node) are compared. Defoliation treatments had no significant effect on yield and on must soluble solids, showing that the remaining leaves were able to guarantee berry development and sugar accumulation in the fruit. The more intense defoliation treatment induced favorable effects on light microclimate in the cluster zone, with positive consequences for polyphenols synthesis and reduction of Botrytis cinerea Pers. incidence